Democracy and belief in conspiracy theories in New Zealand. Issue 3 (3rd July 2022) - Marques, Mathew D.; Hill, Stephen R.; Clarke, Edward J. R.; Williams, Matt N.; Ling, Mathew; Kerr, John R.; Douglas, Karen M.; Cichocka, Aleksandra; Sibley, Chris G.
ABSTRACT : The COVID-19 pandemic supercharged the spread of fake news, misinformation, and conspiracy theories worldwide. Using a national probability sample of adults from the New Zealand Attitudes and Values Study during 2020 (17–99 years old; M  = 48.59, SD  = 13.86; 63% women, 37% men; N  = 41, 487), we examined the associations between agreement with general conspiracy beliefs and political indicators of intention to vote and satisfaction with government, alongside political factors including trust in politicians, political efficacy, identity centrality, and political ideology. Left-wing political ideology, trust in politicians, and political efficacy accounted for most of the explained variance in satisfaction with the government. General conspiracy belief was also a unique contributor to lower satisfaction with the government. We also found a curvilinear relationship between political ideology with heightened belief in conspiracies at both ideological extremes and the centre. Findings are discussed in terms of the consequences of conspiracy belief on democratic engagement.